BIOETIKA PENELITIAN BIOEKOLOGI TUMBUHAN JAMPLONG DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Fitriani; Fhina Marisya Putri; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Bioecological research on jamplong plants in coastal areas is important for understanding the relationship between organisms and their abiotic and biotic environments. Jamplong is a coastal species that can adapt well to extreme environmental conditions such as high salinity, strong winds, and sandy soils. In conducting research, bioethical aspects are an important foundation to ensure that scientific activities do not damage the ecosystem. This study aims to examine the bioecological condition of jamplong plants while also evaluating the application of bioethical principles at Kuranji Beach, West Lombok Regency. The methods used include a literature study and field observations to obtain direct data. The results show that the population of jamplong plants remains abundant with a relatively even distribution in coastal areas, and no violations of bioethical principles were found during the research. This study confirms that bioecological research can be conducted sustainably while still adhering to bioethical principles in order to maintain the balance of coastal ecosystems.